Determine the impact of power and creativity in bringing about organizational change - عباس حسين الحميري; اكرم محسن مهدي الياسري (Iraqi Journal for Administrative Sciences, 2024)
This research aims to determine the impact of organizational power and organizational creativity in bringing about organizational change, and in order to achieve this, power was expressed in the dimensions (legitimate power, information power, experience power, connection power, and reference power) based on Rahim (1989), Kenny (1984). & Wilson), and about creativity in the dimensions of the ability to solve problems and decision-making, the ability to change, the spirit of risk-taking, and encouraging creativity) based on (Ettlic & Okeefe (1982), while organizational change was expressed in the dimensions of changing technology, product and service strategy, structure, and culture based on To (2001, Daft) The field information necessary to complete the research was obtained through a questionnaire prepared for this purpose and distributed to a sample of Karbala Governorate department directors representing their administrative leadership. The research reached a number of conclusions, including: • Proving the first main hypothesis, which states that there are significant correlations between the research variables at a rate of (82.1). • Proving the second main hypothesis, which states that power and creativity influence organizational change by (66.7%). The research concluded with a number of recommendations, including: • Attention to organizational strength and organizational creativity as influential factors in bringing about organizational change through changing the technology used, strategic products and services, structure, and culture. • A call to study other variables that affect organizational change and are not within the scope of the current research. • Testing the research model in other Iraqi governorate departments or other organizations in order to support and generalize the research results.